P‐146: Skin Resistance Measurement using Static Capacitive Touch Panel. Issue 1 (June 2015) - Morimoto, Yuhei; Yoneda, Ryota; Hattori, Reiji
Abstract : We present a novel touch‐sensing system that detects the skin resistance of a touched finger using a static capacitive touch panel. The employed frequency‐scan method enables us to measure skin resistance regardless of touching conditions. The proposed system can create new touch‐sensor applications such as multiuser system and bioelectrical sensing.